Impact of COVID-19 on Hospitality Professionals : Study on Physio-Psychological-Social and Financial Effects - Jamgade, Sweety; Joshi, Neena (Prabandhan: Indian Journal of Management, 2022)
A person’s life is impacted by incidents, accidents, and any events which have their imprints, either physical, mental/psychological, social, or financial. Likewise, the outbreak of the COVID-19 crisis has enormously impacted most people worldwide. Hospitality is one of the worst-hit industries, with a slow recovery business rate. However, no research has been done to study the pandemic’s effect and impact on hospitality professionals’ lives. Hence, this research was undertaken to understand the extent of COVID-19’s effect and impact on the hospitality professionals’ personal lives, including physical, social, and financial aspects. Also, the study aimed to find the feelings that dwell in people either due to isolation, unemployment, or uncertainty . Emotions are related to behavioral responses. Therefore, the qualitative research approach with deductive reasoning was utilized to collect the primary data. Professionals from various service sectors were approached, and responses were analyzed through content and sentiment analysis. The codes and themes were condensed; cases were compared to find the situation’s impacts based on varied employment factors. The findings focused on the sentimental issues of the hospitality working class. The discussions of the study would be helpful to government bodies and hospitality stakeholders in taking proactive measures to counter the unforeseen circumstances of uncertainty . Further studies can be conducted to investigate the deployment of motivational theories to boost the morale of professionals.